Conducting organizational survey and experimental research online: From convenient to ambitious in study designs, recruiting, and data quality. (August 2022) - Van Quaquebeke, Niels; Salem, Mojtaba; van Dijke, Marius; Wenzel, Ramon
Conducting organizational research via online surveys and experiments offers a host of advantages over traditional forms of data collection when it comes to sampling for more advanced study designs, while also ensuring data quality. To draw attention to these advantages and encourage researchers to fully leverage them, the present paper is structured into two parts. First, along a structure of commonly used research designs, we showcase select organizational psychology (OP) and organizational behavior (OB) research and explain how the Internet makes it feasible to conduct research not only with larger and more representative samples, but also with more complex research designs than circumstances usually allow in offline settings. Subsequently, because online data collections often also come with some data quality concerns, in the second section, we synthesize the methodological literature to outline three improvement areas and several accompanying strategies for bolstering data quality. Plain Language Summary: These days, many theories from the fields of organizational psychology and organizational behavior are tested online simply because it is easier. The point of this paper is to illustrate the unique advantages of the Internet beyond mere convenience—specifically, how the related technologies offer more than simply the ability to mirror offline studies. Accordingly, our paper first guides readers through examples of more ambitious online survey and experimental research designs within the organizational domain. Second, we address the potential data quality drawbacks of these approaches by outlining three concrete areas of improvement. Each comes with specific recommendations that can ensure higher data quality when conducting organizational survey or experimental research online.